A origem dos maus-tratos: revisão sobre a evolução histórica das perceções de criança e maus-tratos - Oliveira, Raquel V. (2017)
Aim: In this paper we developed, based on a bibliographical review, an historical perspective on the evolution of the perspectives on child maltreatment and children. We firstly address the concept of maltreatment, then passing through Antiquity and the Middle Ages, where children were subject to constant abuse, being prevalent the physical abuse, sexual abuse and child labour; then progressing to the Modern Age, where the child is seen as having specific characteristics and needing special care. We briefly address the types of maltreatment nowadays and cultural variations. Conclusion: It is crucial to understand the impact that maltreatment has had throughout history and still has nowadays, being essential to consider these aspects in interventions to be developed in this area, taking into particular consideration the wide range of cultural variations increasingly present and evident.